Experimental Analysis of Porter Governor Mechanism in Dynamics of Machinery Laboratory. Issue 1 (August 2021) - Hasan, Ali
Abstract: This work is done in the Machine Dynamics Laboratory of Mechanical Engineering Department. All the observations have been recorded using universal governor apparatus set up available in the laboratory. The author studied both the actual as well as theoretical parameters of the porter governor given to the students to perform their experiments. Author noted that, at M= 1, 2 and 3 kg, the actual sensitivity of given porter governor are 24, 11 and 24% respectively. The actual average sensitivity comes to a value of 20%. While with the help of calculations, the theoretical sensitivity of given porter governor are 23, 17 and 8% respectively. The theoretical average sensitivity comes to a value of 16%. Here, it is to be noted that in both the cases, the sensitivity of the studied governor is constant. The research covers both the experimental and numerical approached. The results of this paper may serve a model for researchers in doing research work as per specific necessity in the early stage of their work.